PEMBERIAN DAGING AYAM DAN BAKING SODA SEBAGAI UPAYA PENINGKATAN KUALITAS KERUPUK AMPLANG - Endang Rusdiana; Budi Santosa (BUANA SAINS, 2006)
The objectives of the study were to determine the best composition between meat chicken and baking soda to obtain quality of amplang chips. The study used Completely Randomized Design (CRD) factorial with two factors. The first factor was chicken meat giff consisting of two levels, i.e. 10 % and 20 %; the second factor was baking soda giff consisting three levels, i.e. 1 %, 2 % and 3 %. The observation was made using physical test consisting of blooming capacity and chemical test consisting of water content, protein content and dust content. The results of this study showed that some levels of baking soda giff obviously influenced blooming capacity and dust content, some levels of chicken meat giff obviously influenced protein content. In water content, the baking soda giff and chicken meat giff treatments showed the obvious different and there were interaction between the two treatments